Syntheses, Reactivities, Characterization, and Crystal Structures of Dipalladium Complexes Containing the 1,3-pyrimidinyl Ligand: Structures of [Pd(PPh(3))(Br)](2)(μ,η(2)-C(4)H(3)N(2))(2), [Pd(Br)](2)(μ,η(2)-Hdppa)(2), and [{Pd(PPh(3))(CH(3)CN)}(2)(μ,η(2)-C(4)H(3)N(2))(2)][BF(4)](2) - Wang, Hsiao-Fen (Molecules, 2020)
In a refluxing chloroform solution, the η(1)-pyrimidinyl {pyrimidinyl = C(4)H(3)N(2)} palladium complex [Pd(PPh(3))(2)(η(1)-C(4)H(3)N(2))(Br)], 1 exhibited intermolecular displacement of two triphenylphosphine ligands to form the doubly bridged η(2)-pyrimidinyl Dipalladium complex [Pd(PPh(3))(Br)](2)(μ,η(2)-C(4)H(3)N(2))(2), 3. The treatment of 1 with Hdppa {Hdppa = N,N-bisdiphenyl phosphinoamine} in refluxing dichloromethane yielded the doubly bridged Hdppa dipalladium complex [Pd(Br)](2)(μ,η(2)-Hdppa)(2), 4. Complex 1 reacted with the bidentate ligand, NH(4)S(2)CNC(4)H(8) and, NaS(2)COEt, and the tridentate ligand, KTp {Tp = tris(pyrazoyl-1-yl)borate}, to form the η(2)-dithio η(1)-pyrimidinyl complex [Pd(PPh(3))(η(1)-C(4)H(3)N(2))(η(2)-SS)], (5: SS = S(2)CNC(4)H(8); 6: SS = S(2)COEt) and η(2)-Tp η(1)-pyrimidinyl complex [Pd(PPh(3))(η(1)-C(4)H(3)N(2))(η(2)-Tp)], 7, respectively. Treatment of 1 with AgBF(4) in acetonitrile at room temperature resulted in the formation of the doubly bridged η(2)-pyrimidinyl dipalladium complex [{Pd(PPh(3))(CH(3)CN)}(2)(μ,η(2)-C(4)H(3)N(2))(2)][BF(4)](2), 8. All of the complexes were identified using spectroscopic methods, and complexes 3, 4, and 8 were determined using single-crystal X-ray diffraction analyses.